Leveraging Indigenous Ikat Heritage for Creative Industry Growth: A Study from Sumba, East Nusa Tenggara - Irma Nuraeni Salsabila; Nico Irawan (Politeknik Siber Cerdika Internasional, 2025)
This mixed-methods study examines the potential of the Sumba Ikat industry in driving creative economy growth in East Nusa Tenggara. Combining in-depth interviews and a structured survey, the research confirms that this authentic art form faces significant structural challenges. Survey data from 85 weavers reveals that only 22% of the weaving population is under 35, signaling a threat to intergenerational continuity. Economically, 56% of weavers earn below one million rupiah monthly, a disparity with the cultural value of their work. A complementary market survey of 35 stakeholders (traders, cooperative managers) indicates that 55% of sales occur through traditional local markets, while online channels account for a mere 7%. Concurrently, the study identifies a significant opportunity: products utilizing natural dyes command market prices up to five times higher than synthetic counterparts. We propose that a strategy of